2019
DOI: 10.1155/2019/2097087
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Outer Choroidal Vasculature in Amblyopia

Abstract: Purpose Several studies have indicated morphological changes in the choroid in amblyopia cases. This study investigates whether choroidal vasculature was different among amblyopic and fellow eyes in unilateral amblyopia patients and healthy eyes, using en face images acquired via swept-source optical coherence tomography (SS-OCT). Design Prospective, observational case-control study. Methods This study included 14 consecutive patients with unilateral amblyopia and 22 age- and axial length-matched healthy eyes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Therefore, novel findings may be obtained by using indices other than BCVA (e.g., accommodation) in the investigation of the relationship between amblyopia and CVD in the future. Several reports have examined choroidal vascular structures in patients with amblyopia [10][11][12][13]. In reports using analyses by binarization of a single-section OCT image, Nishi et al found that the luminal area was significantly larger and the stromal area was significantly smaller in amblyopic eyes than in control hyperopic eyes [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, novel findings may be obtained by using indices other than BCVA (e.g., accommodation) in the investigation of the relationship between amblyopia and CVD in the future. Several reports have examined choroidal vascular structures in patients with amblyopia [10][11][12][13]. In reports using analyses by binarization of a single-section OCT image, Nishi et al found that the luminal area was significantly larger and the stromal area was significantly smaller in amblyopic eyes than in control hyperopic eyes [10].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of analyzing binarized en-face OCT images, Terada et al reported that the outer choroidal vascular areas (i.e., CVD of Haller’s layer) were larger in both amblyopic (61.49 ± 4.95%) and fellow eyes (61.48 ± 3.73%) than in healthy eyes (55.69 ± 1.83%) [ 11 ]. They also indicated that the cutoff for distinguishing between amblyopic patients and controls was 59%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have examined choroidal vascular structures in patients with amblyopia [10,11,12,13]. In reports using analyses by binarization of a single-section OCT image, Nishi et al found that the luminal area was signi cantly larger and the stromal area was signi cantly smaller in amblyopic eyes than in control hyperopic eyes [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new method other than thickness has been developed to evaluate choroidal structures, focusing on choroidal vasculature using binarization analyses [8,9]. Some studies have suggested changes in choroidal vasculature in amblyopic eyes, but insu cient knowledge has been accumulated [10,11,12,13]. The purpose of the present study was thus to investigate the clinical signi cance of evaluating choroidal vascular density (CVD) in patients with amblyopia.…”
Section: Introductionmentioning
confidence: 99%